2005
DOI: 10.1038/sj.ejhg.5201563
|View full text |Cite|
|
Sign up to set email alerts
|

Association study of major risk single nucleotide polymorphisms in the common regulatory region of PARK2 and PACRG genes with leprosy in an Indian population

Abstract: Single nucleotide polymorphisms (SNPs) in the regulatory region shared by PARK2 and PACRG have been identified as major risk factors for leprosy susceptibility in two ethnically distinct populations. We investigated the association of six SNPs present in this regulatory region with leprosy susceptibility in an Indian population. Genotyping was performed by direct PCR sequencing in 286 leprosy patients and 350 healthy controls. Our results showed that T allele of SNPs PARK2_e01 (À2599) and 28 kb target_2_1 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 8 publications
0
19
1
3
Order By: Relevance
“…Although studies have linked PACRG to certain genetic diseases, such as parkinsonism (21,22), leprosy (23,24), and even cancer (25,26), further investigation conclusively established its role in ciliogenesis. Proteomics and biochemical studies revealed that it is a component of Chlamydomonas reinhardtii centriole/basal bodies (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have linked PACRG to certain genetic diseases, such as parkinsonism (21,22), leprosy (23,24), and even cancer (25,26), further investigation conclusively established its role in ciliogenesis. Proteomics and biochemical studies revealed that it is a component of Chlamydomonas reinhardtii centriole/basal bodies (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Several candidate genes including IL10, TLR1, TAP, SLC11A1, have been associated with susceptibility to leprosy and the development of its clinical forms (Malhotra et al 2005;Rajalingam et al 1997;Santos et al 2002;Wong et al 2010a). The association, however, with several loci, such as PARK2-PACRG, LTA and MICA, has not been replicated in many ethnically distinct leprosy affected populations (Hill 2006;Malhotra et al 2006;Wong et al 2010a;Zhang et al 2009). Genome-wide linkage and association studies also have suggested an involvement of multiple risk loci within Histocompatibility antigen (HLA) complex located in 6p21.3 region.…”
Section: Introductionmentioning
confidence: 92%
“…Abnormalities in the promoter region of Parkin/Park2 and PACRG are implicated in various human diseases that include leprosy [12,16,17], typhoid and paratyphoid fever [18], and leukemia [19], as well as in male sterility [5] and ParkinsonÕs disease [3,4]. Considering such a wide range of abnormalities for which PACRG may be responsible, PACRG can be involved in some fundamental cellular function.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was prepared from wild-type C. reinhardtii cells using TRIzol Reagent (Invitrogen) and first strand cDNA was synthesized by SuperScript II reverse transcriptase (Invitrogen) using an oligo(dT) [12][13][14][15][16][17][18] primer. Using it as the template, the cDNAs encoding the full-length and truncated coding sequences of PACRG were amplified by PCR using the primer sets, PACRG_BamHI_F 0 ] (DC2), and PACRG301 + ATG_BamHI_F and PAC-RG693 + 6His_EcoRI_R (DNC2).…”
Section: Expression and Purification Of Recombinant Pacrg Proteinsmentioning
confidence: 99%